THE ROLE OF FINTECH IN THE TRANSFORMATION OF THE ISLAMIC FINANCIAL SECTOR - Nizar, Muhammad; Sukamto, Sukamto; Aslikhah, Aslikhah (Prodi Magister Ekonomi Syariah FEBI UIN Raden Fatah Palembang, 2024)
This study aims to analyze the role of fintech in the transformation of the Islamic financial sector in East Java. Using a descriptive qualitative approach, this study explores how fintech has influenced the accessibility of Islamic financial services, driven product innovation, and faced challenges in its implementation. The results ofthe study show that fintech contributes significantly to expanding Islamic financial inclusion, especially in remote areas, through digital services that facilitate financial transactions. In addition, product innovations such as Islamic crowdfunding and Islamic peer-to-peer financing are increasingly enriching the choice of financial services that are in accordance with Islamic principles. However, the challenges faced include the low digital financial literacy of the community and regulations that do not fully support the development of Islamic fintech. This study recommends increasing digital financial literacy and strengthening more flexible regulations to support fintech innovation in Islamic finance. With this step, it is hoped that fintech can continue to accelerate the transformation of the Islamic financial sector in East Java and expand financial inclusion throughout Indonesia.